Understanding the tourist's response to natural disasters: The case of the 2011 Queensland floods. (January 2015) - Walters, Gabrielle; Mair, Judith; Ritchie, Brent
This article presents the results of a quantitative study designed to investigate the perceptual and behavioural responses of tourists to a disastrous event. Looking specifically at the 2011 Queensland floods, this article explores the image perceptions held by 2113 members of the Australian tourism market in light of this event. It also investigates pull motivations of tourists who claimed they would be willing to visit Queensland despite the flood event. Tourists' past experiences with the state of Queensland, namely their visitation frequency and personal affiliations, are considered in terms of their influence on tourists' attitudes towards visiting the destination and their reasons for doing so. Demographic differences are also explored. The conclusions present marketing implications relating to how to attract the attention of tourists who are willing to visit a destination in the wake of a disastrous event and how to encourage those who are not.